Impact of Persistent Multidrug-Resistant Gram-Negative Bacteremia on Clinical Outcome and Mortality - Shiori Kitaya; Hajime Kanamori; Yukio Katori; Koichi Tokuda (MDPI AG, 2023)
The clinical aspects of persistent bacteremia (PB) caused by gram-negative rods (GNRs) in terms of antimicrobial resistance (AMR) and PB clearance status are unclear. This secondary analysis of a retrospective cohort study investigated differences in PB caused by Enterobacterales and glucose non-fermentative GNRs (NF-GNRs) based on AMR and PB clearance. We retrospectively surveyed medical records at Tohoku University Hospital. Patients for whom blood cultures were performed between January 2012 and December 2021 were recruited. PB cases were grouped based on AMR and PB clearance; the characteristics of PB due to each bacterial pathogen were examined. The main outcome variable was mortality. The late (30-90-day) mortality rate was significantly higher in the multidrug-resistant (MDR) group than in the non-MDR group for Enterobacterales. However, no significant difference was noted in mortality rates between NF-GNRs with and without AMR. Mortality rates tended to be higher in the non-PB-clearance group than in the clearance group for both Enterobacterales and NF-GNRs. Since the mortality rate was higher in the MDR group in the case of Enterobacterales PB, more careful management is necessary for this condition. Follow-up blood cultures and confirming the clearance of PB are useful for improving the survival rate.